Exact Solution for Unsteady Flow of Viscous Incompressible Fluid Over a Suddenly Accelerated Flat Plate (Stokes' First Problem) Using Laplace Transforms - Kharchandy, Spainborlang; ., . (International Journal of Engineering and Technology, 2018)
With the Navier-Stokes Equation in Cartesian form (in absence of body forces), Laplace Transforms provides a simple approach towards solving the unsteady flow of a viscous incompressible fluid over a suddenly accelerated flat plate. On comparing the results between Â Laplace Transforms and similarity methods, it reveals that Laplace Transforms is simple and effective.